Development of a Word Recognition Instrument to Test Health Literacy in Dentistry: The REALD-30 – A Brief Communication - Jessica Y. Lee DDS, MPH, PhD; R. Gary Rozier DDS, MPH; Shoou-Yih Daniel Lee, PhD; (Blackwell Synergy, 2007)
This study aims to develop and pilot test a dental word recognition instrumen.